MOLLUSCUM CONTAGIOSUM, DIAGNOSIS AND TREATMENT - Haeriyoko, Winda Arista; Darmada, IGK. (E-Jurnal Medika Udayana; vol 2 no 7 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Molluscum contagiosum is a dermathology disease caused by molluscum contagiosum virus (MCV), pox viral group from Molluscipox viral genus. The incidence of molluscum contagiosum all over the world aprroximately 2% - 8% with prevalence 5% - 18% in HIV patient.Molluscum contagiosum sendemically spread among rural area, bad hygiene, and low-income population. This disease usually suffered by children, sexually active adult, immunodeficiency patient. Diagnose can be done according to physical examination. Evaluation using central content usig crush and Giemsa or histopatologic if needed. Patient wil spontaneously healed, but after a long time, for months even years. The disease will not residive with eradication of all the lessions will /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: molluscum contagiosum, diagnoses, invasive and non invasive treatment